2022
DOI: 10.1051/0004-6361/202243526
|View full text |Cite
|
Sign up to set email alerts
|

The detection of cluster magnetic fields via radio source depolarisation

Abstract: It has been well established that galaxy clusters have magnetic fields. The exact properties and origin of these magnetic fields are still uncertain even though these fields play a key role in many astrophysical processes. Various attempts have been made to derive the magnetic field strength and structure of nearby galaxy clusters using Faraday rotation of extended cluster radio sources. This approach needs to make various assumptions that could be circumvented when using background radio sources. However, bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Firstly, FR Is are more commonly found in galaxy clusters (Best 2009 ;Gendre et al 2013 ;Croston et al 2019 ) and the strong Faraday depolarization observed there (e.g. Osinga et al 2022 ) means that polarized sources embedded in (and in the background of) these environments are not found at 144 MHz (Carretti et al 2022(Carretti et al , 2023. Secondly, the brightest and most highly polarized regions of FR IIs are at the source extremities, extending well beyond the host galaxy environment in many cases, where they are known to experience lower depolarization (e.g.…”
Section: The Nature Of Polarized Sources At Mhz Frequenciesmentioning
confidence: 99%
“…Firstly, FR Is are more commonly found in galaxy clusters (Best 2009 ;Gendre et al 2013 ;Croston et al 2019 ) and the strong Faraday depolarization observed there (e.g. Osinga et al 2022 ) means that polarized sources embedded in (and in the background of) these environments are not found at 144 MHz (Carretti et al 2022(Carretti et al , 2023. Secondly, the brightest and most highly polarized regions of FR IIs are at the source extremities, extending well beyond the host galaxy environment in many cases, where they are known to experience lower depolarization (e.g.…”
Section: The Nature Of Polarized Sources At Mhz Frequenciesmentioning
confidence: 99%
“…In Figure 11, we showed that the residual power, indicating complexity, was approximately 2× higher in Φ 𝑓 𝑢𝑙𝑙 for continuous distributions with Faraday widths in the range 6 -27 rad m −2 . In comparison, the values of 𝜎 𝑅𝑀 , derived by Osinga et al (2022) based on the depolarization of 819 sources, fell into this range 70% of the time, with a median value of 10 rad m −2 .…”
Section: 𝑚𝑖𝑛mentioning
confidence: 91%